Tinker Belles and evil queens : the Walt Disney Company from the inside out - Griffin, Sean (New York University Press, 2000)
From its Magic Kingdom theme parks to its udderless cows, the Walt Disney Company has successfully maintained itself as the brand name of conservative American family values. But the Walt Disney Company has also had a long and complex relationship to the gay and lesbian community that is only now becoming visible. In Tinker Belles and Evil Queens, Sean Griffin traces the evolution of this interaction between the company and gay communities, from the 1930s use of Mickey Mouse as a code phrase for gay to the 1990s ""Gay Nights"" at the Magic Kingdom. Armed with first-person accounts from Disney